2006
DOI: 10.1007/s11136-006-9000-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among disease-free stomach cancer survivors in Korea

Abstract: Previous studies about the quality of life (QOL) in stomach cancer survivors focused on selected clinical parameters and did not consider the broader implications for overall health and QOL. We evaluated the impact of demographic and treatment-related factors on the QOL of stomach cancer survivors. We asked 391 stage I-III stomach cancer survivors who had been disease-free for at least 1 year after surgery to complete a demographic questionnaire, the European Organization for Research and Treatment of Cancer Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…The association between postprandial symptoms and overly rapid drainage of the stomach was first described by Hertz [13], and the term ‘dumping' was introduced by Mix [14]. Many investigators have reported relationships between gastrectomy type and dumping syndrome [15,16,17,18,19,20,21,22,23], but most such studies were small and focused on only a few types of surgical procedures for gastric cancer. A large-scale study on dumping syndrome after gastrectomy was recently reported [24].…”
Section: Discussionmentioning
confidence: 99%
“…The association between postprandial symptoms and overly rapid drainage of the stomach was first described by Hertz [13], and the term ‘dumping' was introduced by Mix [14]. Many investigators have reported relationships between gastrectomy type and dumping syndrome [15,16,17,18,19,20,21,22,23], but most such studies were small and focused on only a few types of surgical procedures for gastric cancer. A large-scale study on dumping syndrome after gastrectomy was recently reported [24].…”
Section: Discussionmentioning
confidence: 99%
“…The largest studies to date have been cross-sectional, assessing QOL in patients from six months to five years following gastric resection 5, 6, 8, 9 . These well-powered studies concluded that some patients have impaired QOL after curative gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities are important factors in the QoL of survivors of a variety of primary cancers [7, 39, 40]. In this study, we focused on the role of specific comorbidities in the QoL of the cervical cancer survivors.…”
Section: Discussionmentioning
confidence: 99%